Comparison of Anticardiolipin Antibodies Titer in Preeclampsia and Normal Pregnancy: A CaseControl Study - Teimoori, Batool; Noori, Narjes; Ghasemi, Marzieh; Sadeghi, Nayereh; Nurzadeh, Maryam (International Journal of Psychosocial Rehabilitation, 2020)
Background and Aim: Regarding the high prevalence of pre-eclampsia and its complications and also due to conflicting reports about the role of antiphospholipid antibodies, particularly anticardiolipin antibody, the aim of this study was to compare the anticardiolipin antibody titers in pre-eclampsia and normal pregnancy. Material and Methods: In this cross-sectional study, 220 pregnant women in their third trimester were evaluated in Zahedan Ali ebn Abi Talib (AS) hospital in 2013. Participants were divided into two groups: preeclamptic pregnant and normal pregnant as the control group. The sampling method was simple and available. Anticardiolipin IgG and IgM levels were measured in two groups. Samples were analyzed by simple and available methods. An independent t-test was used for data analysis. A p-value less than 0.05 was considered significant. Results: The mean age of pregnant women was 26.1±6.2 years. The gestational age was 37 ± ±2.1 and 1.9 weeks in the control and preeclampsia groups, respectively (P = 0.14). The mean IgM titer of anticardiolipin antibody in the preeclampsia group was 1.85±0.84 μg/L and in the control group 2.21±1.61 μg/L, with no significant difference found between the two groups (P=0.53). The mean IgG titer of anti-cardiolipin antibody in the preeclampsia group was 2.48±1.16 μg/L and in the control group 2.13±0.54 μg/L, and again no statistically significant difference was observed (P=0.34). Conclusions: There was no correlation between anti-cardiolipin antibody titers in pregnant women with preeclampsia compared with normal pregnant women.